ANALISIS HUBUNGAN VARIABEL CUACA DENGAN KEJADIAN DBD DI KOTA YOGYAKARTA - Rinaldi Daswito; Lutfan Lazuardi; Hera Nirwati (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2019)
Dengue Hemorrhagic Fever (DHF) is the main public health issues in Indonesia, even endemic in all provinces. The incidence of DHF is still fluctuated annually in the city of Yogyakarta. This study aims to determine the pattern of the relationship between weather variables (air temperature, rainfall, humidity, and wind speed) on the incidence of DHF in the city of Yogyakarta for 5 years (2010-2014). This study used the ecological study design with spatial-temporal approach. Population was the incidence of dengue for the period 2010-2014 in the administrative area of Yogyakarta city. Spearman-rho correlation test showed that the pattern of the relationship of DHF incidence was more significant (p <0.05) and had a stronger correlation coefficient with an increase in weather variables in the previous few months. Rainfall in the previous two months (r = 0.5617), air temperature three months earlier (r = 0.4399), and humidity in the previous month (r = 0.6097) had a positive relationship pattern with an increase in the incidence of DHF. Wind speed is negatively related to the incidence of DHF in the same month (r = -0.3743). Based on graph/ time-trend analysis and spatial analysis of weather variables had a relationship with the incidence of DHF in the city of Yogyakarta. The Yogyakarta City Health Office is advised to use weather data from BMKG every year in planning DHF prevention programs and determine the timing of mass mosquito eradication (PSN) activities. Keywords: Dengue, vector-borne disease, climate, temporal